Let P 1 ( x ) be the remainder of the polynomial p ( x ) = ( x − 1 ) 2 0 1 7 when divided by another polynomial d ( x ) = x 2 − x + 1 .
If we define P k + 1 ( x ) = P 1 ( P k ( x ) ) for every positive integer k , evaluate P 2 0 1 7 ( 2 0 1 6 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nicely done.
You can even shorten the proof by using:
( x − 1 ) 3 = ( x − 2 ) p ( x ) + 1 ⟹ ( x − 1 ) 3 ≡ 1 m o d p ( x )
Then
( x − 1 ) 2 0 1 7 = ( ( x − 1 ) 3 ) 6 7 2 ( x − 1 ) ≡ x − 1 m o d p ( x )
...
Nicely done.
The first half of the solution seems almost "lucky / magical". Yong's solution provides the mathematical theory to explain how we can compute the answer without having several observations.
Solve d ( x ) = 0 first (using whatever means) to obtain the two roots u = cis 3 π and v = cis 3 − π . Note that p ( u ) = ( u − 1 ) 2 0 1 7 = u − 1 = − v and p ( u ) = ( u − 1 ) 2 0 1 7 = u − 1 = − v . If we let P 1 ( x ) = a x + b for some constants a and b , then we can write p ( x ) = Q ( x ) d ( x ) + a x + b . Substituting x = u and x = v into this result gives − v = a u + b and − u = a v + b . Subtracting the last two equations give u − v = a ( u − v ) ⇒ a = 1 ⇒ b = − u − v = − 1 . Hence P 1 ( 1 ) = x − 1 . Applying this polynomial 2 0 1 7 times to the number x = 2 0 1 6 gives P 2 0 1 7 ( 2 0 1 6 ) = − 1 .
p(x)=(x-1)²⁰¹⁷, d(x)=x²-x+1. Let x-1=t Thus, p(x)=t²⁰¹⁷, d(x)=t²+t+1. Therefore p(x)=t²⁰¹⁷-t+t=t(t²⁰¹⁶-1)+t=t(t²⁰¹³+t²⁰¹⁰+....1)(t-1)d(x)+t. Therefore P1(x)=t=x-1. Pn(x)=x-n
Problem Loading...
Note Loading...
Set Loading...
In this solution, we will apply modular arithmetics properties for polynomials. You can recall them here
Using p ( x ) ≡ 0 m o d p ( x ) we have:
x 2 − x + 1 ≡ 0 m o d p ( x ) ⟺ ( x − 1 ) ≡ x 2 m o d p ( x ) ⟹ ( x − 1 ) 2 0 1 6 ≡ x 4 0 3 2 m o d p ( x )
But
x 3 + 1 = 0 ⟺ ( x + 1 ) ( x 2 − x + 1 ) = 0 ∴ x 3 + 1 ≡ 0 m o d p ( x ) ⟺ x 3 ≡ − 1 m o d p ( x ) ⟹ ( x 3 ) 1 3 4 4 ≡ 1 m o d p ( x )
Hence
( x − 1 ) 2 0 1 6 ≡ 1 m o d p ( x ) ⟺ ( x − 1 ) 2 0 1 7 ≡ ( x − 1 ) m o d p ( x ) ∴ P 1 ( x ) = x − 1
Because d e g ( P 1 ( x ) ) < d e g ( d ( x ) )
Doing the first cases, we can conjecture that P k ( x ) = x − k
Which is clearly true for k = 1
Suppose it is true for a natural number k = n
Then P n ( x ) = x − n which yields
P n + 1 ( x ) = P 1 ( P n ( x ) ) ⟺ P n + 1 ( x ) = ( x − n ) − 1 ⟺ P n + 1 ( x ) = x − ( n + 1 )
∴ P k ( x ) = x − k ■
Therefore, P 2 0 1 7 ( x ) = x − 2 0 1 7 ∴ P 2 0 1 7 ( 2 0 1 6 ) = − 1